FINANCIAL STABILITY OF ISLAMIC AND CONVENTIONAL BANKS IN BANGLADESH: REVISITING STABILITY MEASURES AND ANALYZING STABILITY BEHAVIOR - Hossain, Md. Enayet; Imam, Mahmood Osman (Journal of Islamic Monetary Economics and Finance, 2018)
This study intends to assess the relative financial stability of Islamic banks in Bangladesh using three different Z-Scores as financial stability measures, based on a sample of 29 listed commercial banks (23 conventional and 6 Islamic) in Bangladesh over the period 2005-2016. Apart from the existing measure of financial stability, Z-Score, the paper contributes to the literature by developing an alternative Z-Score based on bank’s loan portfolio infection ratio. We first use pair-wise comparison and find that Islamic banks are financially more stable in two stability measures i.e. Z-Score (based on Capital Adequacy Ratio) and Z-Score (based on Infection Ratio). We then perform static (random effects) and dynamic (GMM) panel data analysis. By controlling for bank-specific, industry-specific and macroeconomic variables in the regressions, we find that Islamic banks are financially more stable in 2 panel regressions of Z-Score (based on Infection Ratio). We also find that the presence of Islamic banks increases the stability of all banks in the system including their conventional peers.